Radiation induced thyroid carcinoma in Romania – effects of the Chernobyl fallout, a systematic review of observational studies - Gábora, Katalin; Bărbuș, Elena; Peștean, Claudiu; Larg, Maria Iulia; Bonci, Eduard Alexandru; Bădulescu, Claudiu Ioan; Piciu, Andra (Medicine and Pharmacy Reports, 2018)
Introduction. The development of thyroid carcinoma is a complex process, in which both genetic and environmental factors play an important role. The rising incidence of thyroid neoplasm determines researchers to investigate factors implicated in this phenomenon. This article aims to elucidate the effects of the Chernobyl nuclear disaster on the Romanian population, studying the existing literature on radiation induced thyroid carcinoma. We analyzed the main studies published on this matter. Methods. We used the PubMed and Google Scholar databases to search for articles upon the effects of the Chernobyl nuclear disaster on the incidence of thyroid carcinoma in the Romanian population. After a careful review of the existing literature, we selected the relevant and accessible studies, the first observation being that data on thyroid related effects of the Chernobyl nuclear disaster are scarce. Results. From the selected studies, results show that there is a possible link between the Chernobyl fallout and the incidence of thyroid carcinoma. Multiple factors have been studied that play an important role in the increasing number of thyroid carcinoma cases, such as: better diagnostic techniques, incidentalomas, microcarcinomas and radiation exposure. In consequence it is difficult to measure the influence that the Chernobyl nuclear fallout has on thyroid carcinoma incidence. Conclusion. Especially in pediatric patients, there seems to be a convincing evidence of radiation related thyroid carcinoma, while in adult patients the rising incidence due exclusively to nuclear fallout is not that clear. Further studies must be done on this matter to clearly see the influence radiation has on the incidence of thyroid cancer.